Evolution of urban morphologies: comparison between Porto (Portugal) and Qazvin (Iran) - Jabbari, Mona (2015)
At present, in major cities, the lack of urban structure cohesion and connectivity promoted by the expansion of street network dominated by cars has increased dramatically. Hence, social life and citizen rights considering anthropocentric and human scale have been put at risk in many cities. â Old Townsâ are perceived as urban structures of the past that are revitalized and given new significance in contemporary cities. The geometrical order of the cities structures shape diverse urban tissue and promote the development in several directions. However, the main activities of the cities occur in the places with the most social interactions. This paper presents an ongoing research that compares the main areas of Porto (Portugal) and Qazvin (Iran), based on the growth of the cities around their historic centers, i.e. â Old townsâ . In-depth review and qualitative analysis are two research approaches for the aim of this research. The obtained results are analyzed and discussed, with potential conclusions identified. The urban form of the cities is analyzed and assessed a methodology based on street pattern identification. Moreover, the outcomes reveal a new pattern for pedestrian network. Moreover, research findings show that the main areas of both cities require new pattern solutions in order to promote connectivity through pedestrian network.